Protocol for a systematic review on interventions for caregivers of persons with mild cognitive impairment and early dementia: does early stage intervention improve caregiver well-being and ability to provide care?. Issue 5 (10th May 2019) - Bayly, Melanie; Morgan, Debra; Kosteniuk, Julie; Elliot, Valerie; Froehlich Chow, Amanda; Peacock, Shelley; McLean, Allen; O'Connell, Megan E
Abstract : Introduction: Caregivers of persons with dementia and mild cognitive impairment (MCI) are at risk of decreased well-being. While many interventions for caregivers exist, evidence is sparse regarding intervention timing and effectiveness at an early stage of cognitive decline. Our systematic review aims to answer the following questions: (1) Do interventions for caregivers of persons with early stage dementia or MCI affect their well-being and ability to provide care? (2) Are particular types of caregiver interventions most effective during early stage cognitive decline? (3) How does effectiveness differ when early and later interventions are directly compared? (4) Do effects of early stage caregiver intervention vary based on care recipient and caregiver characteristics (eg, sex, type of dementia)? Methods and analysis: The databases MEDLINE, EMBASE, PSYCINFO and CINAHL, as well as grey literature databases, will be searched for English language studies using search terms related to caregiver interventions and dementia/MCI. Abstracts and full texts will be screened by two independent reviewers; included studies must assess the effects of an intervention for caregivers of persons with early stage dementia or MCI on caregiver well-being or ability to provide care. Intervention, study and participant characteristics will be extracted by two independent reviewers, along with outcome data. Risk of bias will be assessed using the Cochrane risk of bias tool (for controlled trials with and without randomisation). Interventions will be grouped by type (eg, psychoeducational) and a narrative synthesis is planned due to expected heterogeneity, but a meta-analysis will be performed where possible. The Grading of Recommendations, Assessment, Development and Evaluations approach will be used to inform conclusions regarding the quality of evidence for each type of intervention. Ethics and dissemination: Findings from this review will be disseminated via conferences and peer-reviewed publication, and a summary will be provided to the Alzheimer Society. PROSPERO registration number: CRD42018114960.